Hubungan Faktor-Faktor Motivasi Dengan Kinerja Tenaga Kesehatan Di Puskesmas Siulak Gedang Kecamatan Siulak Kabupaten Kerinci Tahun 2023 - Taqwin, Zalra Muhammad; Guspianto, Guspianto; Nasution, Helmi Suryani (Jurnal Kesmas Jambi, 2023)
Work is an action that is carried out and can produce something that is desired, the work activities carried out are usually called performance. There are 98 health workers working at the Siulak Gedang Health Center. Problems with the performance of health workers can be influenced by the level of motivation obtained by health workers. This type of research is quantitative research. The population in this study were 98 health workers who worked at the Siulak Gedang Health Center, Kerinci Regency, with a total sample of 54 respondents. The sample was taken using the Simple Random Sampling method. Data analysis using Chi Square analysis. There is a relationship between the salary variable and the performance of health workers with a P-Value = 0.039. There is a relationship between the variables of employment status and the performance of health workers with a P-Value = 0.039. There is no relationship between reward and punishment variables and the performance of health workers. There is no relationship between supervision variables and the performance of health workers. There is a relationship between the workload variable and the performance of health workers with a P-Value = 0.046. There is a relationship between the variables of salary, job status and workload on the performance of health workers at the Siulak Gedang Health Center, Kerinci Regency. There is no relationship between the variables of supervision, reward and punishment on the performance of health workers at the Siulak Gedang Health Center, Kerinci Regency.